1998
DOI: 10.1111/j.1945-5100.1998.tb01655.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aouelloul crater, Mauritania: On the problem of confirming the impact origin of a small crater

Abstract: Abstract-The impact origin of small craters in sedimentary rocks is often difficult to confm because of the lack of characteristic shock metamorphic features. A case in point is the 3.1 Ma Aouelloul crater (Mauritania), 390 m in diameter, which is exposed in an area of Ordovician Oujeft and Zli sandstone. We studied several fractured sandstone samples from the crater rim for the possible presence of shock metamorphic effects. In thin section, a large fraction of the quartz grains show abundant subplanar and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Both data sets suggest upward turning of basalt fl ows along the crater wall similar to the impact deformation of target rocks at other simple craters (Shoemaker, 1960;Shoemaker and Eggleton 1961;Brandt and Reimold, 1995;Koeberl et al, 1998;Reimold et al, 1998b). Kumar (2005) also suggested that the major faulting and slumping present at the NNE sector of the crater (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Both data sets suggest upward turning of basalt fl ows along the crater wall similar to the impact deformation of target rocks at other simple craters (Shoemaker, 1960;Shoemaker and Eggleton 1961;Brandt and Reimold, 1995;Koeberl et al, 1998;Reimold et al, 1998b). Kumar (2005) also suggested that the major faulting and slumping present at the NNE sector of the crater (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…(); (14) Taylor (); (15) Smith and Hodge (); (16) Hodge and Wright (); (17) Gurov and Gurova (); (18) Koeberl et al. (); (19) McHone et al. (); (20) Bunch and Cassidy (); (21) Reimold et al.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the glass is similar to that of the sandstone in which the crater is exposed, but some siderophile elements are enriched in the glass (Koeberl and Auer 1991). Re-Os isotope studies of the target sandstone and the impact glass demonstrated the presence of a distinct extraterrestrial component in the glass (Koeberl et al 1998). …”
Section: Samplesmentioning
confidence: 96%
“…The fission track and K-Ar dating of the impact glass show that this crater was formed 3.1 ± 0.3 Ma ago (Fudali and Cressy 1976;Storzer and Wagner 1977). The 390-m-diameter crater is exposed in an area of Ordovician Oujeft quartzite and Zli sandstone (Koeberl et al 1998). Aouelloul impact glasses contain lechatelierite and baddeleyite (El Goresy 1965;El Goresy et al 1968), partly digested quartz and feldspar grains, low water content (Beran and Koeberl 1997), and abundant schlieren of different chemical composition (Koeberl 1994).…”
Section: Samplesmentioning
confidence: 99%